Percepção e juízo: a tese de Kasimir Twardowski sobre Descartes - Pires, Jesuino Junior (2022)
The present thesis proposes to investigate Kasimir Twardowski’s interpretation of the Cartesian theory of evidence based on clear and distinct perception, together with the theory of judgments in his work Idee und Perzeption published in 1892, and to analyze certain positions taken by Twardowski in that written. These positions are relevant because they imply, in view of Franz Brentano’s philosophy, consequences in the distinction between content and object of representation in his later work Zur Lehre vom Inhalt und Gegenstand der Vorstellungen from 1894. This research is characterized as bibliographic research whose procedures are they are based on the logical reconstruction of the philosopher’s arguments in the aforementioned works, on the analysis and interpretation of the problems and subjects discussed. The text is structured in three chapters: the first discusses the classification of psychic phenomena into three fundamental classes: representation, judgment and love and hate, as elaborated by Franz Brentano in 1874 and resumed in 1889, and exposes, in general terms, the purpose and context of the work Psychology from an empirical point of view (1874), with a special dedication to the concepts: intentional “in-existence”, intentional reference and internal perception. The second chapter is dedicated to the work Idee und Perzeption and presents a logical and argumentative reconstruction of this writing, as well as a critical and interpretive analysis showing that Twardowski essentially disagrees with Franz Brentano’s interpretation of René Descartes’ theory of evidence. Twardowski assumes the notion of “presented object” as “immanent object” and uses the term “characteristic” (Merkmal), evidencing a link between the works Idee und Perzeption and Zur Lehre. The last chapter of the text deals with some aspects of the distinction between content and object of presentation present in Twardowski’s 1894 habilitation thesis, and analyzes to what extent this distinction can be found in his doctoral thesis on Descartes, establishing the divergences and the convergences between these two works. The lack of a detailed study in the secondary literature on Idee und Perzeption that discusses the main problems and their relationship with the work Zur Lehre justifies the existence of this research. We infer, therefore, that there is a link between the works Idee und Perzeption and Zur Lehre, due to the treatment of the concept of “characteristic”, the distinction between “being existing” and “being represented” and the reformulation of the idea of “immanent object”